Global vaccine research and application hotspots and trends: a systematic bibliometric analysis based on SCIE highly cited papers - Liming Liang; Xinyu Wang; Yue Zhu; Xu Xia; Runfeng Shi; Huilin Cao; Meixin He; Yuyu Wang; Caizhen You (BMJ Open)
Objectives COVID-19, a public health emergency affecting the world in 2019, not only greatly promoted the development and application of vaccines but also effectively shortened the publishing time of scientific papers. In view of these facts, the current situation, status, problems and development trends of vaccine research and application were explored through bibliometric analysis of highly cited papers in the vaccine field within the time frame of 2014–2024, and the countries, institutions, authors, funding agencies and other relevant information that contributed most to vaccine research and application were summarised.Design Bibliometric analysis through data analysis and visual mapping.Data sources Scientific articles.Data extraction and synthesis ‘Vaccine’ and ‘vaccines’ were used in the WoS database to retrieve the publications and to adequately collect the data; Microsoft Excel was used for data analysis; and VOSviewer was used for visual description of data. Overall publication trends, countries, institutions and funding agencies, authors and articles, journals and languages, and research areas and co-occurrence keywords were analysed by bibliometrics.Results A total of 3258 highly cited papers were published in the field of vaccines in the past decade, from 735 different journals. With the COVID-19 pandemic in 2019, the number of highly cited papers in the field of vaccine research increased significantly from 2020 to 2024, accounting for 76.12%. The number of highly cited papers for vaccines peaked in 2021 and 2022, followed by a rapid decline. Highly cited papers came from 7133 institutions in 153 countries, and the most influential country in the field of vaccines was the USA, which published 1733 highly cited papers, accounting for 53.19% of the highly cited papers. The top 15 institutions with the largest influence were all from the USA or UK with 2567 published papers in total, accounting for 78.79% of highly cited papers. 4787 funding agencies were recognised in funding 2368 highly cited papers. A total of 30 926 authors in 90 research areas contributed significantly to global vaccine research. The most highly cited paper was ‘Safety and Efficacy of the BNT162b2 mRNA COVID-19 Vaccine’ from the New England Journal of Medicine, which was cited 9435 times in total. Among the 9848 co-occurrence keywords, COVID-19 (including SARS-CoV-2, 2019-COVID and SARS2) was the most frequently co-occurrence keyword. It appeared in 1720 articles, accounting for 52.79%, indicating that COVID-19 was the most popular study in the last decade.Conclusions This study visualised the research and application of vaccines in the world from the perspective of papers output, drew the knowledge map and identified the important research hotspots and development trends in the vaccine field in the recent 10 years (2014–2024), which is helpful for Centres for Disease Control and Prevention, clinicians, researchers and health policymakers to better understand the research status and problems in vaccine research and application and predict its future development direction.